2015
DOI: 10.19030/tlc.v12i1.9071
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Lecture Capture On Student Performance In Business Courses

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Academic staff also have concerns about the impact of lecture capture on student performance and attainment, although research findings on the impact of lecture capture on students' learning are mixed: some studies show no impact of lecture capture on learning outcomes (Bosshardt & Chiang, 2016;Franklin, Gibson, Samuel, Teeter & Clarkson, 2011;Williams, Aguilar-Roca & O'Dowd, 2016), whilst others show an increase in academic performance (Cortinhas, 2017;Terry, Macy, Clark & Sanders, 2015;Traphagan et al, 2010). Owston et al (2011) found students who watched more lectures performed less well than those who watched fewer lectures but suggest this may be due to higher achieving students not needing to access so many lectures and lower achieving students lacking confidence, comprehension skills and note taking ability.…”
Section: Literature Review 1perceptions Of Lecture Capturementioning
confidence: 99%
“…Academic staff also have concerns about the impact of lecture capture on student performance and attainment, although research findings on the impact of lecture capture on students' learning are mixed: some studies show no impact of lecture capture on learning outcomes (Bosshardt & Chiang, 2016;Franklin, Gibson, Samuel, Teeter & Clarkson, 2011;Williams, Aguilar-Roca & O'Dowd, 2016), whilst others show an increase in academic performance (Cortinhas, 2017;Terry, Macy, Clark & Sanders, 2015;Traphagan et al, 2010). Owston et al (2011) found students who watched more lectures performed less well than those who watched fewer lectures but suggest this may be due to higher achieving students not needing to access so many lectures and lower achieving students lacking confidence, comprehension skills and note taking ability.…”
Section: Literature Review 1perceptions Of Lecture Capturementioning
confidence: 99%
“…Findings about performance are contradictory though. Some large‐scale studies have established a positive impact on student grades (Hove & Corcoran, ; Traphagan et al ., ; Terry et al ., ), while others found little or no impact (Bollmeier et al ., ; Franklin et al ., ; Leadbeater et al ., ; Hadgu et al ., ); still others underline potential negative side effects (Williams et al ., ; Johnston et al ., ). Leadbeater et al .…”
Section: Why Another Study On Lecture Capture?mentioning
confidence: 99%
“…Many studies involving LC and academic performance have focused on LC availability rather than viewing to identify the impact availability has on academic performance. The following studies reviewed below found LC availability to have a positive impact on academic performance (Dommeyer, 2017;Shaw & Molnar, 2011;Terry et al, 2015;Wiese & Newton, 2013). Dommeyer (2017) compared the academic performance and attendance of 56 students with LC available to 28 students without LC available in separate sections of a marketing research course.…”
Section: Lecture Capture Availability and A Positive Impact On Academ...mentioning
confidence: 99%
“…Williams et al, 2012) Negligible (Bollmeier et al, 2010;Chapin, 2018;Hadgu et al, 2016;Leadbeater et al, 2013;Mallinson & Baumann, 2015;Sarsfield & Conway, 2018;A. Williams et al, 2012) Negative -Lecture recording availability and academic achievement Positive (Dommeyer, 2017;Shaw & Molnar, 2011;Terry et al, 2015;Wiese & Newton, 2013) Negligible (Brotherton & Abowd, 2004;Ford et al, 2012;Traphagan et al, 2010) Negative (Drouin, 2014;Edwards & Clinton, 2019;Johnston et al, 2013) We focused on studies in which lecture recordings were supplemented with in class lectures and only studies including both audio and video recordings were reviewed; outdated studies focusing on the use of audio only podcasts were not included.…”
Section: Studymentioning
confidence: 99%